S02-4 Personal, psychosocial, and biomechanical risk factors for work disability from carpal tunnel syndrome: a pooled prospective study. (1st September 2016) - Adamson, Carisa Harris; Eisen, Ellen; Hegmann, Kurt; Thiese, Matthew; Dale, Ann Marie; Evanoff, Bradley; Kapellusch, Jay; Garg, Arun; Bao, Stephen; Silverstein, Barbara; Gerr, Fred; Rempel, David
Abstract : Introduction: Carpal tunnel syndrome (CTS), the most common peripheral entrapment neuropathy, results from compression of the median nerve at the wrist that leads to more disability than most other upper extremity disorders (Foley 2007). Method: 4321 workers were followed up to 7 years with repeated symptom surveys and nerve conduction studies to identify prevalent and incident cases of CTS (N = 318). Work disability was derived from SF12 and quickDASH questionnaires, and defined as symptom driven: (1) change in work pace, (2) lost time, or (3) job change. Workplace psychosocial exposure was assessed using the Karasek Job Content Questionnaire. Job level biomechanical exposures were time weighted averages of peak hand force, HAL scale, total repetition rate, forceful repetition rate, % time all hand exertions, and% time in forceful hand exertions (≥1 kg-pinch or ≥4 kg-grip). Adjusted hazard ratios were estimated using Cox proportional hazards models. Results: Being female was associated with increased work disability(HR = 1.75; 95% CI: 1.23–2.5) as was having rheumatoid arthritis(HR = 1.85; 95% CI: 1.04–3.26). High job strain compared to low job strain more than doubled the rate of disability (HR = 2.38; 95% CI:1.03–5.51). The HAL Scale (HRmiddle = 3.91;95% CI: 1.82–8.38;HRupper = 3.20; 95% CI: 1.43–7.19), total repetition rate(HRmiddle = 2.30; 95% CI: 1.15–4.58; HRupper = 2.58; 95% CI: 1.23–5.38), % time in forceful exertions (HRupper = 2.03; 95% CI: 1.02–4.05) and% time in all exertions (HRupper = 2.53; 95% CI: 1.17–5.43) were associated with job change. Forceful repetition rate was associated with lost time (HRmiddle = 2.46;95% CI: 1.11–5.48; HRupper = 1.86; 95% CI: 0.91–3.83) and the HAL Scale (HRmiddle = 1.97; 95% CI: 1.24–3.12) and % time in all exertions (HRupper = 1.94; 95% CI: 1.17–3.24) was associated with pace change. Discussion: These results indicate that personal, workplace psychosocial and biomechanical factors are associated with an increased rate of work disability from CTS and should be taken into account for secondary prevention programs.